Does an Overexposure to Democracy in embryo weaken a Constitution in Life? - Lansberg-Rodríguez, Daniela Melaré (2014)
The present paper seeks to establish some relationships between political regimes and constitutional design, putting into debate the notion of the Arab Spring and its extent to explain the regimes changes and authoritarian breakdown. This is why topics as the scope of political participation in constitutional processes and the context of constitutional drafting are reviewed on the lights of the dataset of the Comparative Constitutional Project. The article is divided in five main parts. Firstly, it is contextualized the Arab Spring centered in the process of decision making and the actors related to the process of constitutional design. In the second place, the notions of majority constitutions and constitution compromises are turning in a debate. In the third place, a review of comparative studies about constitutions is presented by emphasize the work of Ackerman and Arato. In the fourth part, the data collected from de Comparative Constitution Project and the Economist Intelligence Unit is presented.Finally, some conclusions are elaborated.